Chapter Magris e la Grecia - Zografidou, Zosi (Biblioteca di Studi di Filologia Moderna, 2021)
Claudio Magris is deeply interested in the classics and Greek culture. The current essay focuses on Magris and Greece through employing two different approaches. On the one hand, it highlights Magris' interest in Greek culture, art and literature. In his works, Magris reflects on the diachronic presence of classical heroes, such as Ulysses or Antigone, within the broader field of world literature. On the other, this essay aims to analysing the reception of Magris' translations in Greece, including the literary criticism of his works.